Evaluation of Automated Blood Microscopy System AI100 with ShonitTM in a Tertiary Care Center in Northern India - Singh, Upinder; Acharya, Shreyam; SEHGAL, TUSHAR (International Journal of Innovative Research in Medical Science, 2024)
Background: The microscopic examination of peripheral blood film is labour-intensive, subjective and time-consuming. It also requires trained technical staff. Technological advancements have been made to develop automated morphological analytical systems for the classification of both red blood cells and white blood cells. We aimed to investigate the ability of the automated microscopy system AI100 with the ShonitTM to examine peripheral blood films. Methods: The study was a prospective study done at the All India Institute of Medical Sciences, New Delhi. We compared the automated morphological analysis system AI100 with ShonitTM with the gold standard of manual microscopy to identify morphological abnormalities in the blood. Results: A total of 108 cases were studied. Twenty-one cases were excluded due to suboptimal staining and smearing. The male-to-female ratio was 7:5, and the median age was 31.1 Years. The Pearson correlation (r) between % of WBCs between AI100 and manual microscopy was 0.92,0.81, 0.34, 0.94 and 0.25 for neutrophils, lymphocytes, monocytes, eosinophils and basophils, respectively. The concordance of AI100 and manual microscopy for microcytes, macrocytes, tear drop cells, target cells, acanthocytes, and echinocytes was 77%, 86%, 100%, 100%,95% and 97%, respectively. The concordance of AI100 and manual microscopy for platelet count, clumps, and giant platelets was 89%,100% and 89%. Conclusions: The automated cell analysis system AI100 with ShonitTM is capable of morphological classification of RBC, WBC and platelet in peripheral blood smears.